South american cadastre 1994-2013 and the vision of cadastre 2014 of the International Federation of Surveyors (Gaceta Técnica, 2015)
The Land management is a highly dynamic activity in municipal management, for which warrants constant monitoring, especially in South America for its high variability from one country to another. This paper explores the situation cadastre in the South American countries, compared to that proposed by the International Federation of Surveyors (FIG) in his vision of Cadastre 2014. It reviewed the literature describing the situation presented in cadastres 10 South American countries in the period 1994-2013. Result is a high variability between the municipal cadastre of the countries studied; highlighting the tax and legal nature thereof. We have observed significant changes legal and political over the past 25 years that impacted on how they manage their cadastral, however, under this review, we conclude that still has not been successful in achieving the six declarations of the vision of FIG Cadastre 2014
Keywords: cadastral evolution; International Federation of Surveyors; FIG